Federal reserve liquidity provision during the financial crisis of 2007-2009 - Michael J. Fleming (Federal Reserve Bank of New York, 2012)
This paper examines the Federal Reserve's unprecedented liquidity provision during the financial crisis of 2007-2009. It first reviews how the Fed provides liquidity in normal times. It then explains how the Fed's new and expanded liquidity facilities were intended to enable the central bank to fulfill its traditional lender-of-last-resort role during the crisis while mitigating stigma, broadening the set of institutions with access to liquidity, and increasing the flexibility with which institutions could tap such liquidity. The paper then assesses the growing empirical literature on the effectiveness of the facilities and provides insights as to where further research is warranted.
Keywords: E58; G01; 330; central bank; liquidity facilities; lender of last resort